2021
DOI: 10.5993/ajhb.45.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Physical Activity, Health-Related Quality of Life, and Weight Stigma in Children in Hong Kong

Abstract: Objectives: Our objective in this study was to establish the relationships among active and inactive physical activity, HRQoL, and weight stigma in children. Additionally, we investigated weight stigma as a mediator of the relationship between physical activity and HRQoL.Methods: This cross-sectional study was conducted in Hong Kong (June 2017-July 2018). Participants were 437 children in elementary school (2 primary schools and 2 non-governmental organizations) and their parents (dyads). Participants complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…Several studies showed that in humans, a shorter adult LTL seems to be related to a suite of differences in behavior, including inactivity, obesity, smoking, alcohol intake, and higher stress reactivity ( Cherkas et al, 2008 ; Costa et al, 2015 ; Mundstock et al, 2015 ; Müezzinler et al, 2016 ; Astuti et al, 2017 ). Although some of these relations are based on single studies and may not be vigorous, physical activity, BMI, and smoking are based on the meta-analyses of many published studies ( Ulaganathan et al, 2018 ; Fairman et al, 2021 ; Kamolthip et al, 2021 ; Leman et al, 2021 ). Also, several studies revealed the possible role of environmental pollutants like air and traffic pollutants on LTL shortening; in a systematic review of more than 12,058 subjects, Zhao B et al revealed that air pollution reduced LTL ( Zhao et al, 2018 ), other studies also reported similar results about air pollution ( Lee et al, 2019 ; Niehoff et al, 2019 ) and this finding was also confirmed in several other studies about the role of traffic pollutants ( Hoxha et al, 2009 ), low to moderate exposure to lead ( Pawlas et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that in humans, a shorter adult LTL seems to be related to a suite of differences in behavior, including inactivity, obesity, smoking, alcohol intake, and higher stress reactivity ( Cherkas et al, 2008 ; Costa et al, 2015 ; Mundstock et al, 2015 ; Müezzinler et al, 2016 ; Astuti et al, 2017 ). Although some of these relations are based on single studies and may not be vigorous, physical activity, BMI, and smoking are based on the meta-analyses of many published studies ( Ulaganathan et al, 2018 ; Fairman et al, 2021 ; Kamolthip et al, 2021 ; Leman et al, 2021 ). Also, several studies revealed the possible role of environmental pollutants like air and traffic pollutants on LTL shortening; in a systematic review of more than 12,058 subjects, Zhao B et al revealed that air pollution reduced LTL ( Zhao et al, 2018 ), other studies also reported similar results about air pollution ( Lee et al, 2019 ; Niehoff et al, 2019 ) and this finding was also confirmed in several other studies about the role of traffic pollutants ( Hoxha et al, 2009 ), low to moderate exposure to lead ( Pawlas et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these dietary patterns, in conjunction with lower levels of physical activity, are in positive associations with childhood obesity ( 1 ). One of the most important factors that is associated with obesity, is sedentary life style and inactivity; too much television watching and video game playing rather than engaging in conventional recreational activities promote obesity in children and adolescents ( 6 9 ). Decrease in physical activity and increased sedentary behavior among children and adolescence is a serious health problem; recent studies have explored that sedentary behaviors among 10–12-year-old children was nearly 8 h per day and they spent more than 2 h per day in front of computer or TV screens ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several lifestyle-related factors are associated with telomere shortening like smoking ( 11 – 13 ), alcohol intake even in minor amounts ( 14 , 15 ), low physical activity ( 16 , 17 ), and high-fat diets ( 18 , 19 ) that trigger telomere shortening. Obesity is a well-known risk factor for many age-related comorbidities and directly increases the risk of oxidative stress and inflammation ( 20 , 21 ). Several previous studies have introduced obesity as a leading cause of telomere shortening ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%